Tocilizumab as a Therapeutic Agent for Critically Ill Patients Infected with SARS‐CoV‐2 - Russell M. Petrak; Nathan C. Skorodin; Nicholas W. Van Hise; Robert M. Fliegelman; Jonathan Pinsky; Vishal Didwania; Michael Anderson; Melina Diaz; Kairav Shah; Vishnu V. Chundi; David W. Hines; Brian P. Harting; et al. (Wiley, 2021)
Tocilizumab is an IL‐6 receptor antagonist with the ability to suppress the cytokine storm in critically ill patients infected with severe acute respiratory syndrome‐coronavirus 2 (SARS‐CoV‐2). We evaluated patients treated with tocilizumab for a SARS‐CoV‐2 infection who were admitted between March 13, 2020, and April 16, 2020. This was a multicenter study with data collected by chart review both retrospectively and concurrently. Parameters evaluated included age, sex, race, use of mechanical ventilation (MV), usage of steroids and vasopressors, inflammatory markers, and comorbidities. Early dosing was defined as a tocilizumab dose administered prior to or within 1 day of intubation. Late dosing was defined as a dose administered > 1 day after intubation. In the absence of MV, the timing of the dose was related to the patient's date of admission only. We evaluated 145 patients. The average age was 58.1 years, 64% were men, 68.3% had comorbidities, and 60% received steroid therapy. Disposition of patients was 48.3% discharged and 29.3% died, of which 43.9% were African American. MV was required in 55.9%, of which 34.5% died. Avoidance of MV (P = 0.002) and increased survival (P < 0.001) was statistically associated with early dosing. Tocilizumab therapy was effective at decreasing mortality and should be instituted early in the management of critically ill patients with coronavirus disease 2019) COVID‐19).